Improvement of the thermal stability of bluish-cyan emitting phosphor Y2MgAl4SiO12:Eu2+ using substitution cations (Zn, Ca, Sr) for white LEDs. Issue 2 (7th December 2021) - Yang, Huifang; Li, Panlai; Ye, Zejun; Huo, Xiaoxue; Wang, Yu; Wu, Qian; Wang, Dawei; Zhao, Jinxin; Wang, Fenghe; Wang, Zhijun
Abstract : A series of bluish-cyan color adjustable phosphors Y2 MgAl4 SiO12 : x Eu 2+ (YMAS) and Y2 (Mg1− y, M y )Al4 SiO12 :Eu 2+ (M = Zn, Ca, Sr) were synthesized by the solid-state method. Abstract : A series of bluish-cyan color adjustable phosphors Y2 MgAl4 SiO12 : x Eu 2+ (YMAS) and Y2 (Mg1− y, M y )Al4 SiO12 :Eu 2+ (M = Zn, Ca, Sr) were synthesized by the solid-state method. The thermal stability can be improved by modifying the cation, especially the thermal stability of Y2 MgAl4 SiO12 :Eu 2+ at 150 °C gradually improved to 92.34% of the original luminescence intensity by introducing Sr 2+ . The white light emitting diode (LED) was fabricated by combining near ultraviolet (NUV) LED chip (370 nm) with a mixture of Y2 Mg0.8 Sr0.2 Al4 SiO12 :0.01Eu 2+ along with green (Ba, Sr)2 SiO4 :Eu and red CaSiAlN3 :Eu in different proportions. A bright warm white LED gives a high color rendering index R a = 96.4, a low correlated color temperature CCT = 4434 K, and CIE chromaticity coordinates at (0.35, 0.34). The results demonstrate that Y2 Mg0.8 Sr0.2 Al4 SiO12 :Eu 2+ phosphor has potential application in the field of white LEDs.